2022
DOI: 10.3390/risks10050104
|View full text |Cite
|
Sign up to set email alerts
|

Financial Planning for Retirement: The Mediating Role of Culture

Abstract: The life expectancy rate of individuals worldwide has risen, and Saudi Arabia is not excluded. Rising long-life expectancy may jeopardize employees’ pensions and reduce the chances of adequate earnings and a decent life after retirement. Moreover, the number of employees, who have paid into pension funds and are now retired, has increased, indicating that pension funds are expected to decrease. Apart from the above, the level of financial literacy in Saudi Arabia was substandard. Therefore, the ultimate object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 71 publications
1
6
0
2
Order By: Relevance
“…These findings are similar to those of Allgood and Walstad (2016). Moreover, these results suggest that the underlying mechanisms through which financial knowledge attenuates FV may differ between objective and self-perceived financial knowledge (Allgood & Walstad, 2016; Ghadwan et al, 2023).…”
Section: Multivariate Analysessupporting
confidence: 79%
“…These findings are similar to those of Allgood and Walstad (2016). Moreover, these results suggest that the underlying mechanisms through which financial knowledge attenuates FV may differ between objective and self-perceived financial knowledge (Allgood & Walstad, 2016; Ghadwan et al, 2023).…”
Section: Multivariate Analysessupporting
confidence: 79%
“…This sample was used as in the A. Ghadwan et al (2022b) study. This specific sample is chosen for the following reasons.…”
Section: Methodology Designmentioning
confidence: 99%
“…In summary for the second research question, it is evident that existing evidence from China has shown that financial education should aim to build confidence in one’s knowledge, and abilities and the future may be a more effective strategy for improving adolescents’ financial literacy (Aulia & Baskoro, 2019; A. Ghadwan et al, 2022; Naufaldi & Baskoro, 2019).…”
Section: Bibliographic Coupling Based On Sources Of Journalsmentioning
confidence: 99%